A Cutting Parameters Selection Method in Milling Aero-Engine Parts Based on Process Condition Matching. (18th December 2013) - Hou, Yongfeng; Zhang, Dinghua; Luo, Ming; Wu, Baohai
Abstract : An optimal selection method of process parameters based on process condition matching is proposed, for the difficulty of the process parameters selection in the milling of complex structure and difficult-to-cut material parts. The factors of process parameters selection are analyzed, process condition vector and process parameter vector are defined, and their quantitative expressions are proposed. The mapping of existing process condition vectors to the process parameter vectors is established, based on the process data accumulated in practical production. Then, process condition matching degree is defined. In the calculation of the matching degree, Analytic Hierarchy Process (AHP) is adopted to determine the affecting weights of process condition factors, and leveling matrix is adopted to eliminate the differences of dimensions and numerical scales between process condition factors. The optimal process parameters are achieved through matching the actual process condition to the existing process condition. A group of typical aero-engine part milling processes is taken as instance, and the feasibility and effectiveness of this method are verified. A typical aero-engine part CNC machining process database system has been designed and developed based on this method.